Strategi Adaptasi Nelayan Tradisional dalam Menghadapi Perubahan Iklim - Putra, Rinaldi Eka; Syafiola, Fedro (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
Climate change presents its own challenges for traditional fishermen in coastal areas of West Sumatra. Fluctuations in environmental conditions and extreme weather affect their catch and income. This study aims to describe the adaptation strategies undertaken by traditional fishermen in the face of climate change impacts. Qualitative research was conducted through in-depth interviews with 15 fishermen in the coastal tourist areas of Carocok, Mandeh, and Sasak. The results showed that most fishermen implement strategies to diversify sources of income, either by expanding fishing areas, fish farming, or seasonal work outside the city in the construction or service sectors. Another strategy implemented is to suppress household consumption patterns by adjusting the type and quantity of food based on fluctuations in income from fishing. Fishermen also take advantage of strong social and familial relationships within the community to help each other overcome economic difficulties. Despite implementing various adaptation strategies, most fishermen still rely heavily on marine resources. Sustainable adaptation planning is needed by considering social, economic, cultural, and gender roles to maintain the sustainability of traditional fishing livelihoods in coastal areas of West Sumatera. Key words: Fishermen. Adaption strategies, and Climate change